Wideband photoacoustic imaging in vivo with complementary frequency conventional ultrasound transducers - Chandramoorthi, Sowmiya; Riksen, Jonas J. M.; Nikolaev, Anton V.; Van Der Steen, Antonius F. W.; Van Soest, Gijs (Frontiers in Physics, 2022)
Photoacoustic (PA) signals are typically broadband in nature. The bandwidth of PA signals depends on the size distribution of the underlying chromophores. Typically, conventional ultrasound (US) transducers, designed for pulse-echo imaging, have limited bandwidth, which reduces their sensitivity to the broadband PA signal. The rejection of out-of-band signals impairs image reconstruction, leading to the loss of image details. Visualization of biological structures, in particular deep targets with a range of sizes requires large acquisition bandwidth. In this work, we combine PA data acquired with two conventional US array probes with complementary frequency bands in order to widen the bandwidth. However, the two conventional transducers also differ in sensitivity and combining the data results in misrepresentation of PA signal strengths. Therefore, in this article we report a novel PA-based method to calibrate the relative sensitivities of the transducers. The proposed method was applied in various scenarios, including imaging vascular structures in vivo. Results revealed that it is feasible to visualize targets varying widely in sizes while combining complementary information acquired with dual US transducers. In addition, the application of sensitivity compensation ratios avoids misrepresentation in the imaging scheme by accounting for sensitivity differences of both transducers during image acquisition.